(untitled) (Periphērica, 2020)
This essay presents a brief analysis of three popular Spanish films released between 2001 and 2012 that are set in the immediate post Civil War period and first decades of the Franco dictatorship. Specifically, it considers three films which aim to reconstruct and represent the experience of the men, women, and children who fought Francoism or who endured repression after the end of the Spanish Civil War: Silencio roto (Armendáriz 2001), El laberinto del fauno (Del Toro 2004), and 30 años de oscuridad (Martín 2012). This essay explores the way in which tropes of politics, history, resistance, and repression are represented in each film, and how filmmakers using popular cinematic forms have appropriated the Spanish Civil War and Franco period settings to comment on contemporary political and social issues in Spain. Most of the recent Spanish cinematic productions (fictional and documentary) that depict the Spanish Civil War and Franco period have focused on the moral vindication of the vanquished. The three films considered here aim to reconstruct the particular experience or memories of the Spanish maquis and topos, and the civilians who supported them in their struggles. Each of the films discussed has sought to play a role in the recasting of collective identity in Spain, and affords important insights into the social processes and experiences of the time in which they were created. In a world where the visual immediacy of cinematic images increasingly works to displace traditional historiography, these representations have become ever more important and merit discussion. This essay takes into account that these cinematic representations are subjective and mediated depictions of events, participants, and circumstances of the Civil War and Franco period, and suggests pedagogical approaches to discussing each film in order to enable students (and other viewers) to grasp how to distinguish between history and the historicizing effect of its representations.